Digitalization of Knowledge in the Islamic Civilization: A ‎History Studies - Paulius Bergaudas (Journal of Comparative Study of Religions, 2022)
The purpose of this study is first to give a comprehensive historical analysis of the preservation and transmission of knowledge in the Islamic civilization from the time of oral transmission to the contemporary era of digitalization. Such analysis provides us with a particular insight for how Muslims should respond to the digitalization of knowledge in the contemporary era. It presents that knowledge digitalization raises a lot of concerns, such as the increasing laziness of students, and decreasing value of knowledge. Through explanatory analysis of secondary sources on the history of knowledge preservation and dissemination, it has been found that in the digitalization of knowledge is not an unprecedented change, rather, in the history of Islamic Civilization, preservation of knowledge went through four different stages: the writing other than the Quran, writing “words of men,” printing press, and the contemporary era of digitalization. The results of this paper present that conservative Islamic response to the technology which changes knowledge preservation is a critical and rational response. Also, it suggests that today Muslims in general, and scholars in particular, should applaud the digitalization of Islamic knowledge, but keep in control of its possible harms.